Emergence of the Zika virus Asian lineage in Angola - Hill,SC; Vasconcelos,J; Neto,Z; Jandondo,D; Zé-Zé,L; Aguiar,RS; Xavier,J; Thézé,J; Mirandela,M; Cândido,ALM; Vaz,F; Sebastião,CDS; et al. (2019)
Research In Context Evidence before this study We searched PubMed without language restrictions using the keywords ‘Zika’ and ‘Africa’ for papers published to October 2018. We also checked available ‘Situation Report’ publications from WHO for evidence of Zika virus (ZIKV) or congenital Zika disease in Africa. ZIKV African lineage has been detected within Africa since the mid 20 th century, yet evidence for spread of the ZIKV Asian lineage within Africa is limited. Two countries in Africa (Cabo Verde and Angola) have reported ZIKV cases that are believed to be caused by a newly introduced Asian lineage virus. Sequence data are critical for confirming and understanding the spread of ZIKV Asian lineage within Africa, but these data are currently limited to a single 193bp fragment of the ZIKV NS1 gene from Angola. In addition, whilst epidemiological data on ZIKV and suspected microcephaly cases have been reported in detail from Cabo Verde, data from Angola are extremely limited. Added value of this study We provide a detailed report of detected ZIKV acute cases and suspected microcephaly cases in Angola. We sequence ZIKV genomes from three acutely infected cases. These represent the first three Asian lineage genomes available from Africa, one of which was acquired from a baby with confirmed microcephaly. Analysis of these sequences suggests that ZIKV may have been introduced to Angola between July 2015 and June 2016, after which it likely circulated for at le